The role of learner character strengths and classroom emotions in L2 resilience - Alrabai, Fakieh; Alamer, Abdullah (Frontiers in Psychology, 2022)
This study aimed to examine a theory-driven model to explain how language learner’s trait emotional intelligence (TEI) and effort as two learner character strengths predict learner enjoyment as a positive emotion and anxiety and boredom as two negative classroom emotions, and how these variables, collectively, predict resilience in language learning. The underlying relationship between these variables were tested via a comprehensive model within positive psychology perspective using the partial least squares structural equation modelling (PLS-SEM) approach. The paths in the final structural model indicated that L2 learner TEI did not significantly explain their resilience directly but rather completely indirectly through the mediation of learner negative and positive emotions. Learner effort directly and indirectly predicted L2 resilience and its predictive power in it was much larger than that of TEI. In addition, enjoyment and boredom directly influenced L2 resilience and also mediated the relationship between learner character strengths and resilience. Anxiety did not significantly predict learner L2 resilience directly since its influence was rather dependent on the role of enjoyment and boredom in L2 resilience. These findings widely support the claims within positive psychology domain that recognize the vital role of character strengths and learner emotions in enhancing L2 learner resilience.